Movement campaign â€œdon't slack! Discipline of wearing a maskâ€ in Poso Regency - Ramadhan, Kadar; Longgupa, Lisda Widianti; Sumiaty, Sumiaty; Nurfatimah, Nurfatimah; Entoh, Christina; Noya, Fransisca; Siregar, Nilda Yulita; Sitorus, Sony Bernike Magdalena; Khuzaifah, Khuzaifah; Lailatul K., Marlina Fitriya (Universitas Muhammadiyah Magelang, 2021)
The number of confirmed cases of Covid-19 in Poso Regency tends to be low. Until this article was written, there were only 19 cases without a death case, of which 18 people have been declared cured and 1 person is still being treated. This condition causes people to be less disciplined in implementing 3M (using masks, maintaining distance, and washing hands). Regarding the use of masks, some argue that they do not have masks and some are not afraid of being infected. Therefore, this activity seeks to campaign for the Don't Slack! Discipline of Wearing Masks for the community goes through the stages of socialization and campaigning for the benefits of using masks, the right types of masks and how to use them, as well as the distribution of masks. This activity was held at 3 central places in Poso City, namely the Central Market, Kasiguncu Market, and the Welcome Kawua Statue. Campaign activities for the â€œDon't Slack! Discipline of Wearing a Maskâ€ has succeeded in educating hundreds of citizens and distributing 1000 masks. It is hoped that with this campaign, people in Poso Regency will be more orderly in complying with health protocols for the prevention of Covid-19.